IN ALISHER NAVOI'S ODES, THE INTERPRETATION OF THE CONNECTION OF THE SEASONS WITH THE NINE STARS AND CONSTELLATIONS - Nazzora Bekzoda; Madina Rakhmatova (Journal Park Publishing, 2023)
In Eastern classical literature, depicting the seasons by comparison with human life is a traditional creative method. Within this tradition, Alisher Navoi goes on the path of a deeper description of the subtle aspects of the human psyche (through inner states) comparing them with the similar aspects of the seasons.